A Theoretical and Empirical Approach to the Value of Information in Risky Markets: A Reply - Antonovitz, Frances; Roe, Terry (The Review of Economics and Statistics, 1988)
Frances Antonovitz, Terry Roe, A Theoretical and Empirical Approach to the Value of Information in Risky Markets: A Reply, The Review of Economics and Statistics, Vol. 70, No. 3 (Aug., 1988), pp. 545-547